Valuing PSAK 64 in Reducing Conservatism in The Extractive Industry - Nella Yantiana; Ricky Ricky; Elok Heniwati (Universitas Hayam Wuruk Perbanas, 2021)
In 2011, the Indonesian Institute of Accountants (IAI) issued PSAK 64, which adopted IFRS 6 concerning exploration for and evaluation of mineral resources. It is assumed that this adoption will improve the quality of financial reporting. This current study examines the impact of PSAK 64 implementation and other related factors on financial statement conservatism. The data were collected by using data from extractive industries listed on the IDX over the period 2009-2010 and 2013-2014 to represent before and after IFRS-based PSAK mandatory implementation respectively. This study develops two regression models to analyze first, factors influence on conservatism before implementing PSAK 64 and second, the influential factors after implementing PSAK 64 by interacting among conservatism factors. The study found that exploration aggressiveness has influenced conservatism and there are no influential factors on conservatism when they interact. Generally speaking, there is a no different level of conservatism before and after implementing PSAK 64. This finding adds a body of literature on the accounting of extractive industry in Indonesia and is prospective for countries having yet adopted IFRS.